Analysis of Microsatellite Allele That potential as Resistance Marker of Giant Gouramy (Osphronemus gouramy Lac.) to Aeromonas hydrophila - Kusumawardhani, Meirina Kartika; Kusumawaty, Diah; Suhandono, Sony (Indonesian Aquaculture Society (MAI), 2014)
Giant gouramy is one of economical important freshwater fish. However, the production of the fish was declined because of a Motile Aeromonas Septicemia (MAS) disease. Giant gouramy with MAS disease caused an ulcer on their skin, and the worst case infection may cause death. The symptoms is vary widely depends on fish resistance to the disease. The aim of this study is to analyze microsatellite alleles that potential as a resistance marker against Aeromonas hydrophila. In previous studies, eleven microsatellite loci were isolated from giant gouramy genome. These loci were tested on DNA from resistant and susceptible giant gouramy that had been treated with Aeromonas hydrophila. Resistant giant gouramy was the gouramy that survived at least 50 days post-infection and ssusceptible giant gouramy was the gouramy that died before 50 days post- infection. Three of eleven microsatellite loci were found with unique alleles that appeared only in resistant giant gouramy and potential as resistance marker, which is the 342 bp allele at GE 1.9 locus with (GCA)10 (ACA) 6 motif, the 262 bp allele at GE 2.4 locus with (GCA) 6 (GGA)10 motif, and the 244 bp allele at GE 1.4 locus with (GCT) 9 (TA) 6 motif. All three loci were used to scan 48 giant gouramy broodstock from Tasikmalaya, Singaparna, and Sukabumi. Amplification of the microsatellite loci was performed by PCR with M13 tail sequence in forward primer and fluorescence dye. Successfully amplified alleles were analyzed with GeneAlEx 6.5 software. As a result, fragment 262 bp and 244 bp that contained in 43.75% of 48 gouramy broodstock predicted have a potency as resistance marker to Aeromonas hydrophila. For further study, microsatellite motifs have to be screened in gouramy progeny, because microsatellites are inhereted in Mendelian traits.